Oxidative Stress and Gene Expression Dynamics: PENK, PDYN, and NRF2 in Cognitive Recovery from Opioid Withdrawal with Herbal Supplements and Aerobic Exercise - Zibandeh Pour, Mahboubeh; Taghian, Farzaneh; Jalali Dehkordi, Khosro (Advanced biomedical research, 2025)
Background: Opioid addiction is a major public health problem that causes impairments in cognitive and oxidative processes. The present study has been designed to investigate the therapeutic potential of aerobic exercise, combined with herbal supplements (Rosa Canina L, Matricaria recutita, and Berberis), on oxidative stress and spatial learning during morphine withdrawal. Materials and Methods: This trial consisted of 45 male C57BL/6 mice, divided into nine groups, with the induction of morphine dependence. Herbal supplements were combined with aerobic exercises for a 4-week intervention. Spatial learning was analyzed using the Morris Water Maze test; oxidative stress biomarkers were measured as superoxide dismutase (SOD), malondialdehyde (MDA), and total oxidative status (TOS); and gene expression levels of proenkephalin (PENK), prodynorphin (PDYN), and nuclear factor erythroid 2-related factor 2 (NRF2) were evaluated using real-time polymerase chain reaction (PCR). Results: Morphine-dependent mice exhibited impaired spatial learning and elevated oxidative stress. Herbal supplements and aerobic exercise, separately, enhanced spatial learning and antioxidant capacity, but the most significant benefits were seen when combined in reducing escape latency and improving SOD and TOS levels. Gene expression analysis revealed that the combination treatment brought PENK, PDYN, and NRF2 levels closer to those of the control group, suggesting synergistic neuroprotective effects. Conclusions: The combination of herbal supplements and aerobic exercise is promising in reducing oxidative stress and improving cognitive recovery during morphine withdrawal. These findings point to a holistic approach in addressing opioid addiction and may inform future clinical applications in improving rehabilitation outcomes and quality of life among affected individuals. Further research is needed to optimize these interventions for broader application.